Um conceito plural: a ἄτη na tragédia grega - Rodrigues, Marco Aurélio [UNESP] (2015)
In the first half of the twentieth century, E. R. Dodds not only stimulated new perspectives through the book The Greeks and the irrational (1953), but also has become the benchmark for future scholars to discuss the concept of ἄτη in the Iliad. Extremely complex, the word ἄτη means in the first instance a blinding stage of human thought and, later, the very accomplished disgrace. Suzanne Saïd (1978) adds that later in classical tragedy, the concept would refer to all sorts of misfortunes. It was R. Doyle (1984) who analyzed the concept in all classical tragedies, just trying to establish its different meanings. Thus, this thesis aims to defend that the concept of ἄτη, along the classical Greek tragedy in the fifth century BC, undergoes changes, assuming different meanings according to the context presented, and may even have lost its original meaning, that the epic and all previous literature recorded. In addition, being united with other terms, the concept of ἄτη achieves new contours and different meanings, which prevents its translation to be fixed at a single semantic field. Hence the proposal, also, to point out that the translation respects the proper use made in each of the tragedies by their authors. Therefore, the argument permeates all the classic tragedies of Aeschylus, Sophocles and Euripides in which the word is present (twenty-eight), in which the term indicates change or addition of semantic value, a fact that will be based on the analysis of the transformation of thought of the Greek man, along the fifth century, underwent extreme changes from the foundation of democracy and the victory against the Persians, until the end of the Peloponnesian War, the fall of the Athenian power and the development of rational thought